A Communicative Approach Towards Increasing Public Knowledge Regarding Halal-Based Products: Communicative Approach Terhadap Peningkatan Pengetahuan Masyarakat Mengenai Produk Berbasis Halal - Mariyani, Mariyani; Nobertson, Ronaldy; Intan A Lawindo, Nur (Universitas Haji Sumatera Utara, 2025)
Halal products are not only a necessity for the Muslim community but also a globally recognized standard for food quality and safety. Although public awareness of the importance of halal products is increasing, there is still a gap in information regarding the criteria, benefits, and how to recognize halal products on the market. This community service activity aims to increase public knowledge and awareness regarding the importance of halal-based products through a communicative approach. In this activity, a communicative approach is used to create effective interactions between presenters and participants through discussions. This method is expected to encourage active community participation, strengthen their understanding, and improve their ability to recognize and select halal products that comply with established standards. The results of the activity indicate that the communicative approach was able to increase public understanding by up to 65%. The main indicators are an increase in the ability to distinguish valid halal labels, an understanding of the halal certification process, and an awareness of the importance of consuming halal products. Thus, this activity makes a positive contribution to public education efforts and supports the creation of a better halal ecosystem.